The Political Economy of Sunni-Shiâah Conflict in Sampang Madura - Hilmy, Masdar (Al-Jamiah Research Centre, 2015)
Many overlooked the fact that politico-economic factors played an important role behind the 2011 and 2012 Sunni-Shiâah conflict in Sampang Madura. Some, however, argue that the Sunni-Shiâah conflict was merely driven by theological factors. The major roots of the conflict thus were therefore the internal dimensions of religious beliefs as contained in its doctrines. As a result, the conflict can only be explained in terms of religious and theological framework. This assumption is commonly shared by the majority of Madurese Muslims by arguing that the island of Madura cannot host the believers of non-Sunni. In the aftermath of the conflict, the community of Shiâah has been forced to seek refuge outside of the land of Madura. By doing so, many observers and the Madurese Muslims tends to have treated political and economic factors as peripheral that exacerbated the escalation of conflict. This article, however, argues vice-versa that it is not theology, but politics and economy, which mainly steered the conflict. Theology played a role in exacerbating the escalation of conflict. During the conflict, religious and theological arguments were deployed as a mobilizing force in order to justify the conflict. Furthermore, the existence of Shiâah community in Sampang is regarded by the mainstream Sunni community as a threat to their long domination over the socio-political structure in that region. The paper, thus, perceives the conflict as the way the local elites maintain the established mode of production. This paper is qualitative research that employs political-economy as its main approach in analyzing the data. [Para pengamat banyak tidak melihat aktor politik dan ekonomi di balik konflik Sunni dan Syiah 2011 dan 2012 di Sampang Madura. Para peneliti bahkan beranggapan bahwa konflik Sunni-Syiah itu dilatari oleh faktor teologis. Ini artinya bahwa tiap kelompok memegang sistem kepercayaan yang berbeda. Akar utama dari konflik itu pada persoalan agama dan doktrinnya yang menyebabkan konflik. Walhasil, konflik hanya bisa dijelaskan dari kerangka keagamaan dan teologis. Asumsi ini banyak dipegang oleh mayoritas Muslim Madura dengan berasalan bahwa orang Madura tidak menerima selain Sunni, termasuk Syiah. Setelah konflik, masyarakat Syiah dipaksa untuk mengungsi ke luar pulau Madura. Dengan begitu, banyak pengamat dan juga masyarakat Muslim Madura melihat faktor politis dan ekonomi hanya pinggiran yang memperparah konflik. Artikel ini beranggapan sebaliknya, bahwa politis dan ekonomi merupakan faktor utama. Teologi hanya memperparah saja. Pada saat konflik, faktor teologis dan agamis digunakan sebagai kekuatan untuk mobilisasi dan menjustifikasinya. Selanjutnya, keberadaan komunitas Syiah di Sampang dianggap sebagai ancaman bagi dominasi Sunni pada struktur sosio politis daerah itu. Artikel ini menganggap bahwa konflik hanyalah sebagai sarana elit lokal untuk mempertahankan dominasi sistem ekonomi. Makalah ini pada dasarnya merupakan penelitian kualitatif yang melihat faktor politis ekonomis sebagai pendekatan dan analisis data].